Acute myocardial infarction induces remodeling of the murine superior cervical ganglia and the carotid body - Ge, Yang; van Roon, Lieke; van Gils, Janine M.; Geestman, Tom; van Munsteren, Conny J.; Smits, Anke M.; Goumans, Marie José T. H.; DeRuiter, Marco C.; Jongbloed, Monique R. M. (Frontiers in Cardiovascular Medicine, 2022)
A role for cardiac sympathetic hyperinnervation in arrhythmogenesis after myocardial infarction (MI) has increasingly been recognized. In humans and mice, the heart receives cervical as well as thoracic sympathetic contributions. In mice, superior cervical ganglia (SCG) have been shown to contribute significantly to myocardial sympathetic innervation of the left ventricular anterior wall. Of interest, the SCG is situated adjacent to the carotid body (CB), a small organ involved in oxygen and metabolic sensing. We investigated the remodeling of murine SCG and CB over time after MI. Murine SCG were isolated from control mice, as well as 24 h, 3 days, 7 days and 6 weeks after MI. SCG and CBs were stained for the autonomic nervous system markers β3-tubulin, tyrosine hydroxylase (TH) and choline acetyltransferase (ChAT), as well as for the neurotrophic factors brain derived neurotropic factor (BDNF), nerve growth factor (NGF) and their tyrosine receptor kinase (pan TRK). Results show that after MI a significant increase in neuron size occurs, especially in the region bordering the CB. Co-expression of TH and ChAT is observed in SCG neuronal cells, but not in the CB. After MI, a significant decrease in ChAT intensity occurs, which negatively correlated with the increased cell size. In addition, an increase of BDNF and NGF at protein and mRNA levels was observed in both the CB and SCG. This upregulation of neurotropic factors coincides with the upregulation of their receptor within the SCG. These findings were concomitant with an increase in GAP43 expression in the SCG, which is known to contribute to axonal outgrowth and elongation. In conclusion, neuronal remodeling toward an increased adrenergic phenotype occurs in the SCG, which is possibly mediated by the CB and might contribute to pathological hyperinnervation after MI.